Effects of stress on neighboring laser written waveguides in gallium lanthanum sulfide - Diener, Romina; Nolte, Stefan; Pertsch, Thomas; Minardi, Stefano (Applied Physics Letters, 2018)
We investigate an observed lack of excitation symmetry of discrete diffraction patterns in periodic arrays of waveguides written by ultrafast laser inscription (ULI) in gallium lanthanum sulfide glasses. We found experimentally that successive waveguides written with identical parameters are detuned from the previous one by Δβ ∼ 0.2-0.5 mm-1. We show that by varying the writing speed of successive waveguides, we increase the symmetry of the array and reduce the detuning by a factor of 2. After careful analysis of possible physical causes, observations suggest that the density of the laser irradiated material is affected by long range stresses induced by ULI.
CRIS-Team Scopus Importer:2023-04-20